New role for R&D the challenge of growth - Jaskolski, Stanley V.
Stanley V. Jaskolski explores the lessons Eaton Corporation has learned from its effort to link technology tightly and seamlessly with the strategies of its business units.
In seeking to aggressively plan new products to grow tomorrow's business, Eaton Corporation has learned a number of lessons. The most important : It's time for R&D to stretch into the role of a business partner for growth.
Internal R&D organizations are in a prime position to contribute to the long-term generation of corporate wealth-and now, more than ever, they are expected to do so. The question that many in the R&D community are wrestling with is how to link technology intimately into this challenge. The author says aim high, at what C.K. Pralahad calls the "opportunity gap," where real gains in growth are waiting to happen. He then lays out some rules, a model and lessons learned in selling and implementing such a program. It's a battle, but well worth the reward; that is, a vital link to the company's businesses and thus to the present and future plans of the corporation.
Keywords: R&D.